Source Mechanism of Monochromatic and Low-Frequency Events at Papandayan volcano, West Java, Indonesia - Hetty Triastuty; Masato Iguchi; Takeshi Tameguri (Institut Teknologi Bandung, 2006)
Monochromatic and low-frequency (LF) seismic events, which occurred in June and July 1998 at Papandayan volcano, were analyzed to make clear their source mechanisms. Monochromatic event is characterized by slowly decaying quasi-sinusoidal coda part. Spectra of monochromatic events have sharp dominant peak in frequency range of 1.4 – 1.8 Hz, while spectra of LF events have broader band (2-5 Hz) than monochromatic events. Epicenters of the monochromatic and LF events are located at the main crater, Mas crater. Focal depths of monochromatic events range 1.5 to 2.0 km, while the depths of LF events are deeper, 2.5 to 4.0 km. Moment acceleration tensors were obtained by inversion of amplitudes distribution of P-wave first motions. Double-couple parts are dominant in both monochromatic and LF events. Fault plane solutions are normal fault types, and the strikes of nodal planes coincide with the directions of geological faults around Mas crater. Isotropic and CLVD parts are not negligible in LF events. Monochromatic and LF events are related to hydrothermal system, because both monochromatic and LF events occurred beneath Mas crater and activation of fumarolic gas emission was observed when seismicity of these events increased. LF events could be generated by normal fault fracturing accompanying fluid movement. Similarities of initial parts of LF to monochromatic events in spectra and source mechanisms suggest that LF events are triggers of quasi-sinusoidal coda parts of monochromatic events.